Faktor Penentu Tarif Pajak Efektif Pada Perusahaan Kesehatan: Sebelum dan Saat Covid-19 - Anindita Dresti Pinastika; Ferry Irawan (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The pandemic of Covid-19 had attacked and contributed to Indonesia's economy negatively. State tax revenues could not be achieved given the restrictions on activities that were intensified to prevent the spread of the virus. Incentives issued by the government are one of the factors causing the decline in state revenues, one of which is in the form of lowering corporate tax rates. The effective tax rate used in measuring corporate tax management is tested with the related-parties transaction, profitability, leverage, and ownership structure variables. The effect of this variable is then compared in 2019 and 2020 to observe whether there is a difference before and during the pandemic. The research was conducted on health sector companies a sector that was positively affected by the pandemic. The results of the study show that leverage has an effect on the effective tax rate (ETR) in 2020 while ownership structure has an effect on the ETR in 2019. The effective tax rate of health sector companies, which allegedly decreased due to incentives from the government, has actually increased during the pandemic.